Analisis Kapasitas Penampang Modifikasi Sungai Pasca Pembangunan Pengamanan Tebing Sungai Kampar Desa Rumbio - Dinda Safitri; Nurdin; Imam Suprayogi (Teknik Sipil Universitas Riau, 2025)
The Kampar River, which flows through Rumbio Village, Kampar Regency, Riau Province, plays a vital role in the hydrological cycle and the sustainability of the surrounding ecosystem. However, the river is prone to flooding, especially during the rainy season, which necessitates technical interventions such as the construction of bank protection structures. This study aims to analyze the cross-sectional capacity of the river after the construction of the bank protection and to evaluate the potential increase in flow capacity through cross-section modification on the opposite side of the constructed bank protection. The methods used include field surveys with echosounder instruments to obtain depth and flow velocity data, calculation of cross-sectional area using the Mean Section method, and analysis of river discharge. The results showed that the highest recorded discharge was 19.47 m³/s, with a cross-sectional capacity of 51.69 m³/s after the construction of the bank protection. Following the cross-sectional modification, the maximum discharge increased to 49.54 m³/s, with a modified cross-sectional capacity of 157.98 m³/s. The study concludes that cross-sectional modification can serve as an effective solution to increase flow capacity and reduce the risk of flooding in the area surrounding the Kampar River in Rumbio Village